PENGARUH PENDIDIKAN KESEHATAN SECARA INDIVIDUAL TENTANG PEMBATASAN ASUPAN CAIRAN TERHADAP PENGETAHUAN TENTANG PEMBATASAN CAIRAN DAN IDWG (INTERDIALYTIC WEIGHT GAIN) PADA PASIEN HEMODIALISIS - Rifka ' Hanum; Sofiana ' Nurchayati; Yesi ' Hasneli N (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract Patient on hemodialysis (HD) should be given health education about fluid intake limitation so that renal function is stable and there will no complications. The purpose of this research was to determine the influence of health education with individual approach about fluid intake limitation towards knowledge about fluid limitation and IDWG (interdialytic weight gain) in patients with hemodialysis. The design of this research was “quasi experiement”. 30 respondents were taken by using purposive sampling method. The instrument used knowledge questionnaire about liquid intake that had been tested for validity and reliability. This research was analyse by univariate and bivariate analysis, dependent and independet t test was used to analysed the data. The most respondents are aged 45-60 years, with the highest percentage on gender was male, last education was high school, most of respondents did not work, moreover the length of HD was 12-60 months. The result showed that health education influences the patient’s knowledge about fluid limitation and IDWG in patients with hemodialysis p value (0,001) < α (0,05). The result of this research recommends to nurses to give health education with individual approach method to increase of knowledge towards patients with hemodialysis about fluid limitation to reduce other complication. Keywords: fluid intake limitation, health education, hemodialysis, individual method, knowledge